SOSIALISASI CHATGPT UNTUK MEMPERMUDAH PEKERJAAN DINAS PPA PEMPROV DKI JAKARTA - Arrachman, Abdul Kholiq; maesaroh, siti; afiyati, Afiyati; Mubarak, Roy; Kurnia, Rizki Ade (Universal Raharja Community (URNITY Journal), 2025)
Abstract : ChatGPT is a language model developed by OpenAI, based on the GPT-3.5 architecture. GPT stands for "Generative Pre-trained Transformer," which indicates that the model is pre-trained to generate text and uses a Transformer architecture. Transformer is a neural network architecture that has proven to be very effective in processing data sequences, such as text. GPT-3.5 is a third generation GPT model that has extraordinary capabilities in understanding and producing text with a high level of intelligence. ChatGPT is specifically designed to support human-machine interactions via text, allowing users to communicate with models using questions or text statements. These models can be used for a variety of purposes, such as responding to questions, generating creative text, or providing assistance in problem solving. In the context of public services or organizations such as the DKI Jakarta Provincial Government's PPA Service, ChatGPT can be integrated as a tool to increase efficiency in communication, provide information, and handle certain tasks automatically. The aim of ChatGPT socialization is to make the work of the DKI Jakarta Provincial Government's PPA Service easier, with the urgency of increasing efficiency and productivity in handling public service tasks. The main aim of this socialization is to introduce and ensure good understanding regarding the use of ChatGPT as a tool in the work of the PPA Service. The targeted output involves increasing the ability of the PPA Service to provide information services, community services, and handling general inquiries through the use of ChatGPT technology. With this outreach, it is hoped that time efficiency can be achieved, service quality improvement and resource optimization in carrying out administrative and communicative tasks.